FAKTOR-FAKTOR PENENTU KEBAHAGIAAN SESUAI DENGAN KEARIFAN LOKAL DI BALI - Bagus Brahma Putra, Gde; Sudibia, I Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.08.NO.01.TAHUN 2019DO - 10.24843/EEB.2019.v08.i01.p05, 2018)
Happiness is one of the new developments in economics. Therefore, economics should talk a lot about individual happiness. This article discusses the factors that determine individual happiness in accordance with local wisdom in Bali. Factors identified in influencing a person's happiness include income, expectations, relationships, faith, gratitude behavior, pro-environment behavior, health, gender, social and cultural capital.